Modeling impacts of climate change on the distribution of invasive Opuntia ficus-indica (L.) Mill. in Ethiopia: Implications on biodiversity conservation. Issue 4 (April 2023) - Hussein, Abdulbasit; Estifanos, Solomon
Abstract: The main danger to biological diversity is the introduction of exotic species. Opuntia ficus-indica ( O. ficus-indica ) is a dangerous invasive species that has seriously harmed Ethiopia's ecology and economy. To properly inform decision-making about the control of this invasive species, it is crucial to investigate the projected invasion dynamics of O. ficus-indica in the country under the current climate change scenarios. Thus, the objective of this research was to evaluate the current distribution and relative importance of environmental variables for O. ficus-indica distribution, map the habitat's future suitability under scenarios of climate change and assess how habitat change would affect the species' future expected suitability in Ethiopia. The SDM R program was used to perform species distribution modeling (SDM) using 311 georeferenced presence records along with climatic variables. Predictive models were developed as an agreement model from six modeling methodologies to investigate the climatic suitability of target species for the years 2050 and 2070 under two shared socio-economic pathway (SSP) scenarios (SSP2-4.5 and 5–8.5) in order to estimate the risks of climate change to the species. Under the current climatic scenario, only 9.26% (104939.3 km 2 ) and 4.05% (45850.6 km 2 ) of the country were moderately and highly suitable for species dispersion and invasion respectively. The remaining 86.69% (980648 km 2 ) was suitable for the distribution and invasion of the species. In 2050, under the SSP2-4.5 and 5–8.5, the highly suitable range of O. ficus-indica is anticipated to expand by 2.30% and 1.76%, whereas the moderately suitable area is predicted to decrease by 1.66% and 2.69%, respectively. Under the SSP2-4.5 and 5–8.5 scenarios, the highly suitable region for the species is expected to grow by 1.47% and 0.65%, respectively, in 2070 compared to the current climatic conditions. This invasive species had already had a considerable negative influence on rangelands in a significant portion of the country with the current cover. Its continuing growth would exacerbate the issue, cause significant economic and environmental harm, and endanger the community's way of living. If preventive and efficient management methods are not taken seriously, the species will have considerable negative environmental impacts, which would be one of the biggest difficulties for pastoralism and their livelihoods.